Molecular modelling and functional studies of the non-stereospecific α-haloalkanoic acid dehalogenase (DehE) from Rhizobium sp. RC1 and its association with 3-chloropropionic acid (β-chlorinated aliphatic acid) - Abdul Hamid, Azzmer Azzar; Wong, Ee Lin; Joyce-Tan, Kwee Hong; Shamsir, Mohd Shahir; Tengku Abdul Hamid, Tengku Haziyamin; Huyop, Fahrul Zaman (Diagnosis Press, 2013)
Many environmental pollutions are caused by the abundance of xenobiotic compounds in nature. For instance, halogenated compounds released from chemical industries were proven to be toxic and recalcitrant in the environment. However, haloalkanoic acid dehalogenases can catalyse the removal of halides from organic haloacids and thus have gained interest for bioremediation and synthesis of industrial chemicals. This study presents the first structural model and the key residues of the non-stereospecific haloalkanoic acid dehalogenase, DehE, from Rhizobium sp. RC1. The enzyme was built using a homology modelling technique; the structure of DehI from Pseudomonas putida PP3 was used as a template, because of its homology to DehE. The structure of DehE consists of only α-helices. Twelve conserved residues that line the active site were identified: Trp34, Ala36, Phe37, Asn114, Tyr117 Ala187, Ser188, Asp189, Tyr265, Phe268, Ile269, and Ile272. These residues are consistent with the residues found in the active site of DehI and D,L-DEX 113 from Pseudomonas sp. 113. Asp189 activates the water molecule as a nucleophile to attack the substrate chiral centre, which would result in an inversion of configuration of either D- or L-substrates. Both D- and L-substrates bind to and interact with the enzyme by hydrogen bonding with three residues, Trp34, Phe37, and Ser188. In addition, a putative tunnel was also identified that would provide a channel for the substrate to access the binding site. Based on computational analysis, DehE was proven to have the substrate affinity towards 3-chloropropionic acid (3CP)/β-chlorinated aliphatic acid, however, its dehalogenation process is far from clear. This DehE structural information will allow for rational design of non-stereospecific haloalkanoic acid dehalogenases in the future.